A study of the underwater acoustic disturbances produced by a ship propeller - KOZACZKA, Eugeniusz (Archives of Acoustics, 1978)
The paper discusses briefly the problem of the generation of underwater acoustic disturbances by hydrodynamic sources 3. g. a ship propeller). The results of the investigations carried out in a hydrodynamic channel are presented. They refer to the following characteristics: the amplitude spectrum of the disturbances, the propeller performance (characteristic), and the acoustic pressure level as a function of the propeller speed at given velocities of movement relative to the undisturbed water. The results of investigations performed in an anechoic basin are described. They are illustrated by the amplitude spectra of the acoustic disturbances recorded using a narrow-band analyser with a bandwidth of 3.16 Hz. In addition, the level of the acoustic underwater disturbances as a function of the propeller rotational speed is discussed. Having in mind certain limitations imposed upon the experiments per-formed in a hydrodynamic channel and an anechoic basin the measurements of acoustic underwater disturbances at the marine conditions were carried. The electrically driven ship propeller was used. The results discussed in this paper concern a propeller operating in the presence of cavitation. In addition to the results of these investigations a method is also presented for studying the acoustic effects produced by a ship propeller working under various conditions.